A method for preparing carbon / semi-coke adsorption material using asphalt as carbon source
By combining asphalt with oil shale semicoke, carbon/semicoke adsorption materials are prepared by strong alkali activation and calcination methods, the problem of uneven adsorption performance in the prior art is solved, and efficient dye wastewater treatment is achieved.
Patent Information
- Application Number
- CN202310956233.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-08-01
AI Technical Summary
The prior art is difficult to effectively use oil shale semicoke as a carbon source to prepare high-performance adsorbents, resulting in uneven adsorption performance.
Carbon/semicoke adsorption materials are prepared by combining the strong alkali activation and calcination method of oil shale semicoke. The method includes ball milling, hydrothermal synthesis, alkali activation and high-temperature calcination, etc., to ensure uniform bonding of carbon and semicoke.
The efficient preparation of carbon/semi-coke adsorption materials is achieved, which significantly improves its specific surface area, pore volume and adsorption performance, and has efficient adsorption ability for cationic and anionic dyes in industrial dye wastewater.
Smart Images

Figure CN116747840B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization and relates to a method for preparing a carbon / semi-coke adsorption material by taking asphalt as a carbon source. Background Art
[0002] Carbon adsorbents play an important role in emerging environmental governance technologies. Compared with traditional adsorbents, they have opened up new avenues for the application of new technologies in water treatment due to their high specific surface area, good chemical and thermal stability, easy chemical or physical modification, adjustable properties for special applications, and special ability to remove organic and inorganic pollutants. Therefore, the research on carbon adsorbents and their composite materials has made amazing progress and has become a very hot topic in the pursuit of innovation. In recent years, in order to reduce the pollution caused by the stacking and burning of agricultural waste and industrial solid waste, many carbon-based adsorbents have emerged using solid wastes rich in carbon sources (such as straw, fruit shells, needle coke, textile sludge, asphalt, oil shale semi-coke, etc.) to remove dyes or heavy metal ions in water.
[0003] Oil shale semi-coke (SC) is the solid waste left after crude oil is extracted from oil shale. The storage of large amounts of SC not only occupies fields, but also, with the erosion of rainwater, sulfur, polycyclic aromatic hydrocarbons, heavy metal ions and other toxic pollutants in SC may penetrate into the soil, causing more extensive ecological and environmental damage. SC is mainly composed of burnout and inorganic matter. The former is mainly residual organic components and inorganic carbon; the latter mainly includes SiO2, Al2O3, Fe2O3 and CaO, and the corresponding crystal phases are quartz and kaolinite, hematite and carbonate, etc. SC has an irregularly arranged microcrystalline lamellar structure and is rich in developed micropores. However, due to the presence of tar and ash residues on the surface of SC, a large number of micropores are blocked, making its specific surface area smaller, and the alkanes and alkenes in the tar are hydrophobic, making it difficult to achieve effective contact with water-soluble dyes in aqueous solution, and the adsorption capacity is relatively low, so it is not suitable for direct use as an adsorbent to remove pollutants in water bodies. Using semi-coke as the skeleton to load activated carbon and prepare semi-coke activated carbon adsorbent is one of the important directions for preparing SC-based high-efficiency adsorbents.
[0004] Patent CN111167407A (application number: CN202010048329.0, applicant: Shaanxi University of Science and Technology) provides a method for preparing semi-coke activated carbon adsorbent by KOH alkali melting method, which is: taking KOH and washing semi-coke and mixing them evenly, and carbonizing them at high temperature under the protection of inert gas to prepare semi-coke activated carbon adsorbent. However, due to the low content of organic matter that can be converted into carbon in semi-coke, the content of activated carbon in the prepared adsorbent is limited. In order to improve the activated carbon source, researchers have mixed semi-coke with agricultural and forestry biomass waste (Wang Aiqin et al., patent CN110523373A), corn stalks (Liu Hongpeng, Gong Shishang, Jia Chunxia, Wang Qing, Research on the Mixed Combustion Characteristics of Oil Shale Semi-coke and Corn Stalks, Science Technology and Engineering, 2016, 16 (25): 278-285), and camellia oleifera shells (Zhang Can, Experimental Study on Mixed Combustion of Camellia oleifera Shells and Oil Shale / Semi-coke, South China University of Technology, 2016) to improve the adsorption performance of semi-coke. However, the solid phase interface bonding between these carbon source materials and semi-coke during the mixed calcination process is poor, and most of them show a mechanical mixture of two solid particles of activated carbon and semi-coke. Therefore, the defect is that the mixing uniformity of the two solid phase materials is not good, and the distribution uniformity of pore size and specific surface area is poor, so that the semi-coke activated carbon material shows uneven adsorption performance. In summary, it is necessary to find a carbon source that can form a uniform interface bonding with semi-coke to prepare semi-coke high carbon adsorbent.
[0005] Coal tar pitch (CTP), referred to as coal tar, is the residue after coal tar distillation and extraction, and is a major by-product in the deep processing of coal tar. Its basic components are polycyclic and condensed aromatic hydrocarbons and their derivatives. With the extensive application of coal tar, environmental testing has made a wide range of assessments on the environmental and human health hazards that coal tar may cause. It is found that its polycyclic aromatic hydrocarbons are carcinogenic to humans after entering water bodies, soil and other environments. Therefore, the research and development of healthy and environmentally friendly high-value products has become the main direction of coal tar research and development and application. Since the carbon content in coal tar is as high as 80%, it is used as a carbon resource to prepare porous carbon materials, which has received more and more attention and research. Patent CN 101214944A (application number: CN200710173126.9, applicant: Donghua University) discloses a method for preparing a high-strength coal tar pitch carbon foam material. The main steps are to prepare a mesophase pitch by pyrolysis of coal tar pitch, and then obtain a pitch carbon foam material by extraction, drying, foaming, carbonization and other steps. The carbonized material prepared by this method has a large specific surface area and high strength, but the asphalt needs to be extracted through the intermediate phase, and the preparation process is relatively complicated. Some researchers directly mix coal tar with inorganic particles, and the template effect of inorganic particles can effectively improve the strength and porosity of asphalt carbonized materials. Currently reported inorganic phase particles include nano-MgCO3 (Zhang Jianhua, Qiao Song, Qiao Wenming, et al. Preparation of asphalt-based mesoporous carbon and its adsorption properties [J]. Journal of Materials Science and Engineering, 2010, 28(05): 716-720.), nano-ZnO (Zhang Tao, Zhang Ya, Jiao Yurong. Preparation of medium and low temperature coal tar pitch-based porous carbon and its adsorption properties for neutral red [J]. Chemical Technology, 2022, 30(02): 6-11.), nano-calcium carbonate (Zhong Cungui, Deng Shaobo, Guo Liang Cheng, et al. Preparation of asphalt-based carbon materials by template method and study of their adsorption properties for phenol [J]. Functional Materials, 2014, 45(11): 11140-11143), magnesium-aluminum hydrotalcite (Zhang Li. Preparation of asphalt-based porous carbon and study of its adsorption properties for dyes [D]. Ma'anshan: Anhui University of Technology, 2017.), calcium oxide (Wang Liang. Preparation of hierarchical porous carbon by calcium oxide template method and study of its adsorption properties for dyes in wastewater [D]. Ma'anshan: Anhui University of Technology, 2018.), etc. Coal tar pitch has good adhesion to inorganic phase particles, and the prepared porous carbon materials all show good adsorption properties. However, to date, there has been no research report on using coal tar pitch directly as a carbon source and semi-coke as an inorganic phase to prepare carbon / semi-coke high-activity adsorbents. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a new carbon / semi-coke adsorbent material using asphalt as a carbon source. On the one hand, it provides a high value-added conversion pathway for producing new carbon materials using coal tar asphalt as a carbon source, and on the other hand, it also provides a strategy for preparing high-performance adsorbents from industrial waste oil shale semi-coke.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source comprises the following steps:
[0009] Step 1:
[0010] 1.1 Weigh oil shale coke particles and solid NaOH particles, the mass ratio of oil shale coke to solid NaOH is 1: (1.5-4);
[0011] 1.2 ball-milling the weighed oil shale coke particles and solid NaOH particles to uniformly mix the oil shale coke and NaOH and grind them into fine powder to obtain a first mixture;
[0012] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0013] Step 2:
[0014] 2.1 The obtained second mixture was transferred into a beaker, and water was added into the beaker, the mass ratio of the second mixture to water being 1:2; at room temperature, the mixture was stirred with a magnetic stirrer at a stirring speed of 300 rpm for 3 h to 6 h to obtain a third mixture;
[0015] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 180-240°C, and the temperature is kept for 20-30 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and the first reaction product is taken out;
[0016] 2.3 After washing the first reaction product with deionized water until it is neutral, the washed first reaction product is dried to obtain a solid product, which is oil shale semi-coke after alkali activation, marked as MSC;
[0017] Step 3:
[0018] 3.1 Weigh MSC particles, coal tar pitch particles and solid KOH particles. The mass ratio of MSC, coal tar pitch and solid KOH is 1:(1-2):(1-3);
[0019] 3.2 ball-milling the weighed MSC particles, coal tar pitch particles and solid KOH particles to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0020] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0021] Step 4:
[0022] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 600-900°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 600-900°C, the material in the furnace is calcined at a high temperature of 600-900°C for 1-3 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0023] 4.2 Sulfuric acid is added to the second reaction product to adjust the pH value to 6-7; the mixture of the second reaction product and sulfuric acid is then centrifuged in a centrifuge, the supernatant is removed, and the solid product is finally dried to obtain the final product carbon / semi-coke adsorption material, which is marked as CM.
[0024] In the above step 1.1, the particle size of the oil shale semi-coke is through a 10-mesh sieve, and the particle size of the solid NaOH is through a 10-mesh sieve.
[0025] In the above step 1.2, the process of ball milling the oil shale semi-coke particles and the solid NaOH particles is as follows:
[0026] The weighed oil shale semi-coke particles and solid NaOH particles are placed in an agate ball mill, and then agate grinding balls are placed. The agate grinding balls include large balls and small balls. The diameter of the large balls is 2 cm, the diameter of the small balls is 1 cm, and the mass ratio of the large balls to the small balls is 1:(1.5-2); the mass ratio of the grinding balls to the materials is 3:1;
[0027] The agate ball mill jar is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture.
[0028] In the above step 2.3, the washed first reaction product is placed in an oven and dried at a temperature of 110°C.
[0029] In the above step 3.1, the particle size of MSC is through a 10-mesh sieve, the particle size of coal tar pitch is through a 10-mesh sieve, and the particle size of solid KOH is through a 10-mesh sieve.
[0030] In the above step 3.2, the process of ball milling MSC particles, coal tar pitch particles and solid KOH particles is as follows:
[0031] The weighed MSC particles, coal tar pitch particles and solid KOH particles are placed in an agate ball mill, and then agate grinding balls are placed. The agate grinding balls include large balls and small balls. The diameter of the large balls is 2 cm, the diameter of the small balls is 1 cm, and the mass ratio of the large balls to the small balls is 1:(1.5-2); the mass ratio of the grinding balls to the materials is 3:1;
[0032] The agate ball mill jar was then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture.
[0033] In the above step 4.2, the volume concentration of sulfuric acid is 2% to 3%.
[0034] In the above step 4.2, the mixture of the second reaction product and sulfuric acid is placed in a centrifuge, and the centrifuge is centrifuged at a speed of 4500r / min for 20min, and then the supernatant is removed, and finally the solid product is placed in an oven and dried at 110°C to obtain the final product carbon / semi-coke adsorption material.
[0035] The beneficial effects of the present invention are as follows:
[0036] 1. Coal tar pitch is rich in carbon source and is a high-quality carbon raw material. Coal tar pitch is in a molten state after heating, and has good fluidity, permeability and adhesion. These excellent properties provide very sufficient conditions for the close combination of coal tar pitch and oil shale semi-coke interface, and provide a strong guarantee for the uniform coating of activated carbon on the semi-coke surface.
[0037] 2. Oil shale semi-coke has a multi-dimensional lamellar structure and micropores, and the pretreatment of oil shale semi-coke in the first step of the present invention can further increase the specific surface area and voids of oil shale semi-coke, providing sufficient interface for the penetration and adhesion of coal tar pitch. Oil shale semi-coke is the skeleton of the adsorbent, which effectively improves the strength and specific surface area of the adsorbent.
[0038] 3. The present invention can realize the co-conversion of solid waste coal tar pitch and oil shale semi-coke, thereby achieving the dual value of environmental protection and profit.
[0039] 4. The carbon / semi-coke adsorption material prepared by the present invention is used in the field of industrial dye wastewater treatment, and mainly adsorbs cationic dye methylene blue (MB) and anionic dye Congo red (CR) dissolved in water.
[0040] 5. The carbon / semi-coke adsorption material prepared by the present invention can achieve a saturated adsorption capacity of 915.25 mg / g for methylene blue (MB) at room temperature (25°C), and a saturated adsorption capacity of 459.98 mg / g for Congo red (CR) at room temperature (25°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a bar chart comparing the experimental results of the experimental group I, control group I, experimental group II and control group II of the present invention. DETAILED DESCRIPTION
[0042] The purpose of the present invention is to provide a method for preparing a carbon / semi-coke adsorbent material using asphalt as a carbon source, using oil shale semi-coke as a matrix and coal tar pitch as a carbon source, and combining strong alkali activation with calcination to prepare a novel carbon / semi-coke based composite adsorbent for treating dye wastewater. The specific operation steps are as follows:
[0043] Step 1:
[0044] 1.1 Weigh oil shale coke particles and solid NaOH particles, the mass ratio of oil shale coke to solid NaOH is 1:(1.5-4); wherein, the particle size of oil shale coke is through a 10-mesh sieve, and the particle size of solid NaOH is through a 10-mesh sieve;
[0045] 1.2 Put the weighed oil shale semi-coke particles and solid NaOH particles into an agate ball mill, and then put in agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2 cm, the diameter of the small ball is 1 cm, and the mass ratio of the large ball to the small ball is 1: (1.5-2); the mass ratio of the grinding ball to the material is 3:1;
[0046] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture;
[0047] After the oil shale coke and solid NaOH are fully ball-milled, the oil shale coke and solid NaOH can be in contact with each other over a large area;
[0048] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0049] Step 2:
[0050] 2.1 The obtained second mixture was transferred into a beaker, and water was added into the beaker, the mass ratio of the second mixture to water being 1:2; at room temperature, the mixture was stirred with a magnetic stirrer at a stirring speed of 300 rpm for 3 h to 6 h to obtain a third mixture;
[0051] The main components of oil shale semi-coke (SC) are kaolinite (molecular formula Al2Si2O5(OH)4) and quartz (molecular formula SiO2), both of which are silicon-rich compounds. They react with NaOH to form water-soluble sodium silicate, which can effectively improve porosity and increase specific surface area. Water can dissolve NaOH and generate a large amount of heat, promote the penetration of strong alkali and strengthen the reaction between strong alkali and silicon compounds, and dissolve the product sodium silicate from the SC matrix. Using a magnetic stirrer to stir at a stirring speed of 300 rpm for 3h to 6h is an effective guarantee for completing the above reaction and dissolving the product.
[0052] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 180-240°C, and the temperature is kept for 20-30 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and the first reaction product is taken out;
[0053] The third mixture is transferred into a polytetrafluoroethylene high-pressure reactor for hydrothermal synthesis. The principle is that the evaporation of water at high temperature increases the pressure in the polytetrafluoroethylene high-pressure reactor. The oil shale coke (SC) is in a strong alkali, high temperature and high pressure closed environment, which further increases the digestion of insoluble substances and increases the voids on the first reaction product, which is conducive to the coal tar pitch in step 3 to adhere to the MSC particles and penetrate into the voids of the MSC particles.
[0054] 2.3 After washing the first reaction product with deionized water to neutrality (pH=7), the washed first reaction product is placed in an oven and dried at 110° C. The obtained solid product is alkali-activated oil shale semi-coke, which is marked as MSC;
[0055] Step 3:
[0056] 3.1 Weigh MSC particles, coal tar pitch particles and solid KOH particles, the mass ratio of MSC, coal tar pitch and solid KOH is 1:(1-2):(1-3); wherein the particle size of MSC particles is through a 10-mesh sieve, the particle size of coal tar pitch particles is through a 10-mesh sieve, and the particle size of solid KOH particles is through a 10-mesh sieve;
[0057] 3.2 Put the weighed MSC particles, coal tar pitch particles and solid KOH particles into an agate ball mill, and then put in agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2 cm, the diameter of the small ball is 1 cm, and the mass ratio of the large ball to the small ball is 1: (1.5-2); the mass ratio of the grinding ball to the material is 3:1;
[0058] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0059] After MSC, coal tar pitch and solid KOH are fully ball-milled, MSC, coal tar pitch and solid KOH can be in contact with each other over a large area;
[0060] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0061] Step 4:
[0062] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 600-900°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 600-900°C, the material in the furnace is calcined at a high temperature of 600-900°C for 1-3 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0063] The principle of calcining the fifth mixture is that coal tar pitch generally softens at 40-70°C and melts at 300°C. If coal tar pitch is mixed and ground evenly with MSC and then calcined at high temperature, the coal tar pitch melts and flows, which is not only easy to wrap on the surface of MSC particles, but also penetrates into the micro-sheets and micropores of MSC to form a strong CTP / MSC interface bond. Through high-temperature calcination under Ar protection, coal tar pitch is converted into activated carbon, which can achieve the coating of the carbon adsorption layer of MSC to obtain a carbon / semi-coke adsorbent. Among them, the purpose of adding solid KOH is to dissolve the carbon layer and MSC matrix in a high temperature environment, create more voids and cavities, increase the specific surface area, and increase the number of adsorption sites.
[0064] 4.2 Sulfuric acid is added to the second reaction product to adjust the pH value to between 6 and 7, wherein the volume concentration of the sulfuric acid is 2% to 3%; then the mixture of the second reaction product and the sulfuric acid is placed in a centrifuge, and the centrifuge is centrifuged at a speed of 4500 r / min for 20 minutes, the supernatant is removed, and finally the solid product is placed in an oven and dried at 110° C. to obtain the final product carbon / semi-coke adsorption material, which is marked as CM.
[0065] The present invention is described in detail below through specific embodiments.
[0066] Example 1
[0067] A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source comprises the following steps:
[0068] Step 1:
[0069] 1.1 Weigh 10g of oil shale coke particles and 15g of solid NaOH particles; the particle size of the oil shale coke particles is through a 10-mesh sieve, and the particle size of the solid sodium hydroxide particles is through a 10-mesh sieve;
[0070] 1.2 Put 10g of oil shale semi-coke particles and 15g of solid NaOH particles into an agate ball mill, and then put in 75g of agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:1.5;
[0071] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture;
[0072] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0073] Step 2:
[0074] 2.1 Take 20 g of the second mixture and transfer it into a beaker, and add 40 g of water into the beaker; stir the mixture at room temperature with a magnetic stirrer at a stirring speed of 300 rpm for 6 h to obtain a third mixture;
[0075] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 180°C, and the oven temperature is kept at 180°C for 30 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and then the first reaction product is taken out;
[0076] 2.3 After washing the first reaction product with deionized water to neutrality (pH=7), the washed first reaction product is placed in an oven and dried at 110° C. The obtained solid product is alkali-activated oil shale semi-coke, which is marked as MSC;
[0077] Step 3:
[0078] 3.1 Weigh 5g of MSC particles, 5g of coal tar pitch particles and 5g of solid KOH particles; wherein the particle size of MSC particles is through a 10-mesh sieve, the particle size of coal tar pitch particles is through a 10-mesh sieve, and the particle size of solid KOH particles is through a 10-mesh sieve;
[0079] 3.2 Put 5g MSC particles, 5g coal tar pitch particles and 5g solid KOH particles into an agate ball mill, and then put in 45g agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:1.5;
[0080] The agate ball mill jar was then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0081] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0082] Step 4:
[0083] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 600°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 600°C, the material in the furnace is calcined at a high temperature of 600°C for 3 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0084] 4.2 Sulfuric acid was added to the second reaction product to adjust the pH value to 7, wherein the volume concentration of sulfuric acid was 2%; then the mixture of the second reaction product and sulfuric acid was placed in a centrifuge, and the centrifuge was centrifuged at a speed of 4500 r / min for 20 min, the supernatant was removed, and finally the solid product was placed in an oven and dried at 110°C to obtain the final product carbon / semi-coke adsorption material, which was marked as CM-①.
[0085] Example 2
[0086] A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source comprises the following steps:
[0087] Step 1:
[0088] 1.1 Weigh 10g of oil shale coke particles and 20g of solid NaOH particles; the particle size of the oil shale coke particles is through a 10-mesh sieve, and the particle size of the solid sodium hydroxide particles is through a 10-mesh sieve;
[0089] 1.2 Put 10g of oil shale semi-coke particles and 20g of solid NaOH particles into an agate ball mill, and then put in 90g of agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:1.5;
[0090] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 12 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture;
[0091] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0092] Step 2:
[0093] 2.1 25 g of the obtained second mixture was transferred into a beaker, and 50 g of water was added to the beaker; the mixture was stirred at room temperature with a magnetic stirrer at a stirring speed of 300 rpm for 5 h to obtain a third mixture;
[0094] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 200°C, and the oven temperature is kept for 24 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and then the first reaction product is taken out;
[0095] 2.3 After washing the first reaction product with deionized water to neutrality (pH=7), the washed first reaction product is placed in an oven and dried at 110° C. The obtained solid product is alkali-activated oil shale semi-coke, which is marked as MSC;
[0096] Step 3:
[0097] 3.1 Weigh 5g of MSC particles, 5g of coal tar pitch particles and 10g of solid KOH particles; wherein the particle size of MSC particles is through a 10-mesh sieve, the particle size of coal tar pitch particles is through a 10-mesh sieve, and the particle size of solid KOH particles is through a 10-mesh sieve;
[0098] 3.2 Put 5g MSC particles, 5g coal tar pitch particles and 10g solid KOH particles into an agate ball mill, and then put in 60g agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:1.5;
[0099] The agate ball mill jar was then fixed in a planetary ball mill and ground at a speed of 110 rpm for 12 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0100] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0101] Step 4:
[0102] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 700°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 700°C, the materials in the furnace are calcined at a high temperature of 700°C for 2 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0103] 4.2 Add sulfuric acid to the second reaction product to adjust the pH value to 6, wherein the volume concentration of sulfuric acid is 3%; then put the mixture of the second reaction product and sulfuric acid into a centrifuge, centrifuge at a speed of 4500r / min for 20min, remove the supernatant, and finally put the solid product into an oven and dry it at 110°C to obtain the final product carbon / semi-coke adsorption material, marked as CM-②.
[0104] Example 3
[0105] A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source comprises the following steps:
[0106] Step 1:
[0107] 1.1 Weigh 10g of oil shale coke particles and 30g of solid NaOH particles; the particle size of the oil shale coke particles is through a 10-mesh sieve, and the particle size of the solid sodium hydroxide particles is through a 10-mesh sieve;
[0108] 1.2 Put 10g of oil shale semi-coke particles and 30g of solid NaOH particles into an agate ball mill, and then put in 120g of agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:2;
[0109] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 13 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture;
[0110] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0111] Step 2:
[0112] 2.1 35 g of the obtained second mixture was transferred into a beaker, and 70 g of water was added to the beaker; the mixture was stirred at room temperature with a magnetic stirrer at a stirring speed of 300 rpm for 4 h to obtain a third mixture;
[0113] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 240°C, and the temperature is kept for 20 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and the first reaction product is taken out;
[0114] 2.3 After washing the first reaction product with deionized water to neutrality (pH=7), the washed first reaction product is placed in an oven and dried at 110° C. The obtained solid product is alkali-activated oil shale semi-coke, which is marked as MSC;
[0115] Step 3:
[0116] 3.1 Weigh 5g of MSC particles, 7.5g of coal tar pitch particles and 15g of solid KOH particles; wherein the particle size of MSC particles is through a 10-mesh sieve, the particle size of coal tar pitch particles is through a 10-mesh sieve, and the particle size of solid KOH particles is through a 10-mesh sieve;
[0117] 3.2 Put 5g MSC particles, 7.5g coal tar pitch particles and 15g solid KOH particles into an agate ball mill, and then put in 82.5g agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:2;
[0118] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 15 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0119] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0120] Step 4:
[0121] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 800°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 800°C, the material in the furnace is calcined at a high temperature of 800°C for 2 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0122] 4.2 Sulfuric acid was added to the second reaction product to adjust the pH value to 7, wherein the volume concentration of sulfuric acid was 3%; then the mixture of the second reaction product and sulfuric acid was placed in a centrifuge, and the centrifuge was centrifuged at a speed of 4500 r / min for 20 min, the supernatant was removed, and finally the solid product was placed in an oven and dried at 110°C to obtain the final product carbon / semi-coke adsorption material, which was marked as CM-③.
[0123] Example 4
[0124] A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source comprises the following steps:
[0125] Step 1:
[0126] 1.1 Weigh 10g of oil shale coke particles and 40g of solid NaOH particles; the particle size of the oil shale coke particles is through a 10-mesh sieve, and the particle size of the solid sodium hydroxide particles is through a 10-mesh sieve;
[0127] 1.2 Put 10g of oil shale semi-coke particles and 40g of solid NaOH particles into an agate ball mill, and then put in 150g of agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:2;
[0128] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 15 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture;
[0129] 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture;
[0130] Step 2:
[0131] 2.1 40 g of the obtained second mixture was transferred into a beaker, and 80 g of water was added to the beaker; the mixture was stirred at room temperature with a magnetic stirrer at a stirring speed of 300 rpm for 3 h to obtain a third mixture;
[0132] 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 180°C, and the oven is kept warm for 26 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and then the first reaction product is taken out;
[0133] 2.3 After washing the first reaction product with deionized water to neutrality (pH=7), the washed first reaction product is placed in an oven and dried at 110° C. The obtained solid product is alkali-activated oil shale semi-coke, which is marked as MSC;
[0134] Step 3:
[0135] 3.1 Weigh 5g of MSC particles, 10g of coal tar pitch particles and 15g of solid KOH particles; wherein the particle size of MSC particles is through a 10-mesh sieve, the particle size of coal tar pitch particles is through a 10-mesh sieve, and the particle size of solid KOH particles is through a 10-mesh sieve;
[0136] 3.2 Put 5g MSC particles, 10g coal tar pitch particles and 15g solid KOH particles into an agate ball mill, and then put in 90g agate grinding balls. The agate grinding balls have large balls and small balls. The diameter of the large ball is 2cm, the diameter of the small ball is 1cm, and the mass ratio of the large ball to the small ball is 1:2;
[0137] The agate ball mill is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 15 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture;
[0138] 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture;
[0139] Step 4:
[0140] 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 900°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 900°C, the material in the furnace is calcined at a high temperature of 900°C for 1 hour; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature;
[0141] 4.2 Add sulfuric acid to the second reaction product to adjust the pH value to 6, wherein the volume concentration of sulfuric acid is 2%; then put the mixture of the second reaction product and sulfuric acid into a centrifuge, centrifuge at a speed of 4500r / min for 20min, remove the supernatant, and finally put the solid product into an oven and dry it at 110°C to obtain the final product carbon / semi-coke adsorption material, marked as CM-④.
[0142] The parameters of the surface area, pore volume and average pore diameter of the oil shale semi-coke and the carbon / semi-coke adsorption materials prepared in the four embodiments of the present invention are shown in Table 1:
[0143] Table 1
[0144]
[0145] It can be seen from Table 1 that the surface area and pore volume of oil shale semi-coke (SC) are very small, and it has macropores with an average pore size of 13.604 nm. These properties indicate that the surface of SC provides few active sites for adsorbing dyes, resulting in low adsorption. The surface area S of the adsorbent material carbon / semi-coke (CM) prepared by the present invention using asphalt as the carbon source and semi-coke as the matrix BET Significantly increased to over 2200m 2 / g, and the pore volume also increased to more than 1.20cm 3 / g, and the average pore size is about 2 nm, indicating that CM has a large surface area and abundant pores, so the adsorption performance of dyes is significantly improved.
[0146] The adsorption effect of the carbon / semi-coke adsorption material prepared by the present invention is demonstrated by adsorption experiments below:
[0147] Experiment 1,The experiment was divided into two groups, namely, experimental group Ⅰ and control group Ⅰ;
[0148] Experimental Group I: The carbon / semi-coke adsorbent (CM) prepared by the present invention was used to adsorb the dye MB solution (cationic dye), and the equilibrium adsorption amount of the carbon / semi-coke adsorbent was calculated. The specific operation steps are as follows:
[0149] 1. First weigh 10.0 mg of carbon / semi-coke adsorbent (prepared by the present invention) and 25 ml of dye MB solution (dye MB is produced by Tianjin Zhiyuan Chemical Reagent Co., Ltd., molecular weight 373.90, analytical grade);
[0150] 2. Use a UV-visible photometer to measure the concentration of the dye MB solution under the condition of a maximum absorption wavelength of 665 nm, that is, the concentration of the dye MB solution before adsorption, recorded as C 0(MB) ;
[0151] 3. Then, 10.0 mg of carbon / semi-coke adsorbent and 25 ml of dye MB solution were weighed and stirred evenly in a beaker, and the beaker was placed in a shaker (THZ-98A, Shanghai, China) and shaken at 150 rpm for 24 hours at a reaction temperature of 25°C.
[0152] 4. Finally, the concentration of the dye MB solution in the beaker was measured using a UV-visible photometer at a maximum absorption wavelength of 665 nm, that is, the concentration of the dye MB solution after adsorption, recorded as C e(MB) ;
[0153] 5. Calculate the equilibrium adsorption capacity Q of carbon / semi-coke adsorbent e(MB) (mg / g), calculated as follows:
[0154]
[0155] Among them, C 0(MB) (mg / L) is the initial concentration of the dye MB solution; C e(MB) (mg / L) is the concentration of the dye MB solution after the dye MB is adsorbed by the carbon / semi-coke adsorbent; V (MB) (ml) is the volume of the dye MB solution, that is, 25 ml; M (CM) (mg) is the mass of the carbon / semi-coke adsorption material, that is, 10.0 mg.
[0156] Results of Experimental Group I:
[0157] The experimental results of CM-① prepared in Example 1 of the present invention through the above adsorption experimental method are as follows:
[0158] C 0(MB) =511.14mg / L; C e(MB) =229.48mg / L;
[0159] According to formula (1), we get Q e(MB) =704.15mg / g.
[0160] The experimental results of CM-② prepared in Example 2 of the present invention through the above adsorption experimental method are as follows:
[0161] C 0(MB) =511.14mg / L; C e(MB) =161.67mg / L;
[0162] According to formula (1), we get Q e(MB) =873.68mg / g.
[0163] The experimental results of CM-③ prepared in Example 3 of the present invention through the above adsorption experimental method are as follows:
[0164] C 0(MB) =511.14mg / L; C e(MB) =145.04mg / L;
[0165] According to formula (1), we get Q e(MB) =915.25mg / g.
[0166] The experimental results of CM-④ prepared in Example 4 of the present invention through the above adsorption experimental method are as follows:
[0167] C 0(MB) =511.14mg / L; C e(MB) =146.24mg / L;
[0168] According to formula (1), we get Q e(MB) =912.25mg / g.
[0169] Control group I: Use oil shale coke (SC) to adsorb dye MB solution (cationic dye) and calculate the equilibrium adsorption amount of oil shale coke (SC). The specific experimental steps are as follows:
[0170] 1. First weigh 10.0 mg of oil shale semi-coke particles and 25 ml of dye MB solution (dye MB is produced by Tianjin Zhiyuan Chemical Reagent Co., Ltd., molecular weight 373.90, analytical grade), recorded as M (SC) =10.0mg, V (MB) =25ml;
[0171] 2. Use a UV-visible photometer to measure the concentration of the dye MB solution under the condition of maximum absorption wavelength of 665nm, that is, the concentration of the dye MB solution before adsorption, C 1(MB) =511.14mg / L;
[0172] 3. Then, 10.0 mg of oil shale semi-coke particles (SC) and 25 ml of dye MB solution were mixed evenly in a beaker, and the beaker was placed in a shaker (THZ-98A, Shanghai, China) and shaken at a speed of 150 rpm for 24 hours at a reaction temperature of 25°C.
[0173] 4. Finally, use a UV-visible photometer to measure the concentration of the dye MB solution in the beaker under the condition of a maximum absorption wavelength of 665nm, that is, the concentration of the dye MB solution after adsorption, C 2(MB) =502.36mg / L;
[0174] 5. Calculate the equilibrium adsorption amount Q of oil shale semi-coke particles sc(MB) (mg / g), calculated as follows:
[0175]
[0176] Get: Q sc(MB) =21.95mg / g.
[0177] Experiment 2: The experiment was divided into two groups, experimental group II and control group II.
[0178] Experimental Group II: The carbon / semi-coke adsorbent (CM) prepared by the present invention was used to adsorb the dye CR solution (anionic dye), and the equilibrium adsorption amount of the carbon / semi-coke adsorbent was calculated. The specific operation steps are as follows:
[0179] 1. First weigh 10.0 mg of carbon / semi-coke adsorbent (prepared by the present invention) and 25 ml of dye CR solution (dye CR is produced by Shanghai Zhongqin Chemical Reagent Co., Ltd., molecular weight 696.68, analytical grade);
[0180] 2. Use a UV-visible photometer to measure the concentration of the dye CR solution under the condition of a maximum absorption wavelength of 497 nm, that is, the concentration of the dye CR solution before adsorption, recorded as C 0(CR) ;
[0181] 3. Then, 10.0 mg of carbon / semi-coke adsorbent and 25 ml of dye CR solution were weighed and stirred evenly in a beaker, and the beaker was placed in a shaker (THZ-98A, Shanghai, China) and shaken at 150 rpm for 24 h at a reaction temperature of 25°C.
[0182] 4. Finally, use a UV-visible photometer to measure the concentration of the dye CR solution in the beaker under the condition of a maximum absorption wavelength of 497nm, that is, the concentration of the dye CR solution after adsorption, recorded as C e(CR) .
[0183] 5. Calculate the equilibrium adsorption capacity Q of carbon / semi-coke adsorbent e(CR) (mg / g), calculated as follows:
[0184]
[0185] Among them, C 0(CR) (mg / L) is the initial concentration of the dye CR solution; C e(CR) (mg / L) is the concentration of the dye CR solution after the carbon / semi-coke adsorbent adsorbs the dye CR; V (CR) (ml) is the volume of the dye CR solution, that is, 25ml; M (CM)(mg) is the mass of the carbon / semi-coke adsorption material, that is, 10.0 mg.
[0186] Results of experimental group II:
[0187] The experimental results of CM-① prepared in Example 1 of the present invention through the above adsorption experimental method are as follows:
[0188] C 0(CR) =269.71mg / L; C e(CR) =134.93mg / L;
[0189] According to formula (3), we get Q e(CR) =336.95mg / g.
[0190] The experimental results of CM-② prepared in Example 2 of the present invention through the above adsorption experimental method are as follows:
[0191] C 0(CR) =269.71mg / L; C e(CR) =109.40mg / L;
[0192] According to formula (3), we get Q e(CR) =400.78mg / g.
[0193] The experimental results of CM-③ prepared in Example 3 of the present invention through the above adsorption experimental method are as follows:
[0194] C 0(CR) =269.71mg / L; C e(CR) =85.72mg / L;
[0195] According to formula (3), we get Q e(CR) =459.98mg / g.
[0196] The experimental results of CM-④ prepared in Example 4 of the present invention through the above adsorption experimental method are as follows:
[0197] C 0(CR) =269.71mg / L; C e(CR) =92.42mg / L;
[0198] According to formula (3), we get Q e(CR) =443.23mg / g.
[0199] Control group II: Use oil shale coke (SC) to adsorb dye CR solution (anionic dye) and calculate the equilibrium adsorption amount of oil shale coke (SC). The specific experimental steps are as follows:
[0200] 1. First weigh 10.0 mg of oil shale semi-coke particles and 25 ml of dye CR solution (dye CR produced by Shanghai Zhongqin Chemical Reagent Co., Ltd., molecular weight 696.68, analytical grade), recorded as M (SC) =10.0mg, V (CR) =25ml;
[0201] 2. Use a UV-visible photometer to measure the concentration of the dye CR solution under the condition of maximum absorption wavelength of 497nm, that is, the concentration of the dye CR solution before adsorption, C 1(CR) =269.71mg / L;
[0202] 3. Then, 10.0 mg of the oil shale semi-coke particles and 25 ml of the dye CR solution were mixed evenly in a beaker, and the beaker was placed in a shaker (THZ-98A, Shanghai, China) and shaken at 150 rpm for 24 h at a reaction temperature of 25 °C;
[0203] 4. Finally, use a UV-visible photometer to measure the concentration of the dye CR solution in the beaker under the condition of a maximum absorption wavelength of 497nm, that is, the concentration of the dye CR solution after adsorption, C 2(CR) =265.88mg / L;
[0204] 5. Calculate the equilibrium adsorption amount Q of oil shale semi-coke particles sc(CR) (mg / g), calculated as follows:
[0205]
[0206] Get: Q sc(CR) =9.58mg / g.
[0207] The experimental results (equilibrium adsorption amount) of the above experimental group I, control group I, experimental group II and control group II are statistically calculated as follows: Figure 1 The bar graph shown is from Figure 1 It can be seen that the carbon / semi-coke adsorbents prepared in Examples 1 to 4 of the present invention have high equilibrium adsorption capacities for both MB and CR, which are significantly higher than the adsorption capacities of oil shale semi-coke SC.
Claims
1. A method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source, characterized in that: The following steps are included: Step 1: 1.1 Weigh oil shale coke particles and solid NaOH particles, the mass ratio of oil shale coke to solid NaOH is 1: (1.5-4); 1.2 ball-milling the weighed oil shale coke particles and solid NaOH particles to uniformly mix the oil shale coke and NaOH and grind them into fine powder to obtain a first mixture; 1.3 Then the first mixture is passed through a 100-mesh sieve to obtain a second mixture; Step 2: 2.1 The obtained second mixture was transferred into a beaker, and water was added into the beaker, the mass ratio of the second mixture to water being 1:2; at room temperature, the mixture was stirred with a magnetic stirrer at a stirring speed of 300 rpm for 3 h to 6 h to obtain a third mixture; 2.2 Then the third mixture is transferred into a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven, the oven temperature is set to 180-240°C, and the temperature is kept for 20-30 hours; after the reaction is completed, the polytetrafluoroethylene autoclave is cooled naturally, and the first reaction product is taken out; 2.3 After washing the first reaction product with deionized water until it is neutral, the washed first reaction product is dried to obtain a solid product, which is oil shale semi-coke after alkali activation, marked as MSC; Step 3: 3.1 Weigh MSC particles, coal tar pitch particles and solid KOH particles. The mass ratio of MSC, coal tar pitch and solid KOH is 1:(1-2):(1-3); 3.2 ball-milling the weighed MSC particles, coal tar pitch particles and solid KOH particles to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture; 3.3 Then the fourth mixture is passed through a 100-mesh sieve to obtain a fifth mixture; Step 4: 4.1 The fifth mixture is placed in a tube furnace, and a protective atmosphere Ar is introduced into the furnace, and the gas flow rate of Ar is 100 sccm; the temperature in the furnace is increased to 600-900°C at a heating rate of 5°C / min; when the temperature in the furnace reaches 600-900°C, the material in the furnace is calcined at a high temperature of 600-900°C for 1-3 hours; after the calcination is completed, the ventilation is stopped, and the second reaction product is taken out from the tube furnace and naturally cooled to room temperature; 4.2 Sulfuric acid is added to the second reaction product to adjust the pH value to 6-7; the mixture of the second reaction product and sulfuric acid is then centrifuged in a centrifuge, the supernatant is removed, and the solid product is finally dried to obtain the final product carbon / semi-coke adsorption material, which is marked as CM.
2. According to claim 1, a method for preparing a carbon / semi-coke adsorption material using asphalt as a carbon source is characterized in that: In the step 1.1, the particle size of the oil shale semi-coke is through a 10-mesh sieve, and the particle size of the solid NaOH is through a 10-mesh sieve.
3. The method for preparing carbon / semi-coke adsorption material using asphalt as a carbon source according to claim 1, characterized in that: In step 1.2, the process of ball milling the oil shale semi-coke particles and the solid NaOH particles is as follows: The weighed oil shale semi-coke particles and solid NaOH particles are placed in an agate ball mill, and then agate grinding balls are placed. The agate grinding balls include large balls and small balls. The diameter of the large balls is 2 cm, the diameter of the small balls is 1 cm, and the mass ratio of the large balls to the small balls is 1:(1.5-2); the mass ratio of the grinding balls to the materials is 3:1; The agate ball milling jar is then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the oil shale semi-coke and NaOH and grind them into fine powder to obtain a first mixture.
4. The method for preparing carbon / semi-coke adsorption material using asphalt as a carbon source according to claim 1, characterized in that: In the step 2.3, the washed first reaction product is placed in an oven and dried at a temperature of 110°C.
5. The method for preparing carbon / semi-coke adsorption material using asphalt as a carbon source according to claim 1, characterized in that: In the step 3.1, the particle size of MSC is through a 10-mesh sieve, the particle size of coal tar pitch is through a 10-mesh sieve, and the particle size of solid KOH is through a 10-mesh sieve.
6. The method for preparing carbon / semi-coke adsorption material using asphalt as a carbon source according to claim 1, characterized in that: In step 3.2, the process of ball milling the MSC particles, the coal tar pitch particles and the solid KOH particles is as follows: The weighed MSC particles, coal tar pitch particles and solid KOH particles are placed in an agate ball mill, and then agate grinding balls are placed. The agate grinding balls include large balls and small balls. The diameter of the large balls is 2 cm, the diameter of the small balls is 1 cm, and the mass ratio of the large balls to the small balls is 1:(1.5-2); the mass ratio of the grinding balls to the materials is 3:1; The agate ball mill jar was then fixed in a planetary ball mill and ground at a speed of 110 rpm for 10 to 15 minutes to uniformly mix the MSC, coal tar pitch and solid KOH and grind them into fine powder to obtain a fourth mixture.
7. The method for preparing carbon / semi-coke adsorption material using asphalt as a carbon source according to claim 1, characterized in that: In step 4.2, the volume concentration of sulfuric acid is 2% to 3%.
8. The method for preparing carbon / semi-coke adsorption material using pitch as a carbon source according to claim 1, characterized in that: In the step 4.2, the mixture of the second reaction product and sulfuric acid is placed in a centrifuge, and the centrifuge is centrifuged at a speed of 4500r / min for 20min, and then the supernatant is removed, and finally the solid product is placed in an oven and dried at 110°C to obtain the final product carbon / semi-coke adsorption material.
Citation Information
Patent Citations
Method for preparing high-strength coal tar asphalt carbon foam material
CN101214944A
Preparation method of oil shale semi-coke adsorbent
CN110523373A
Semicoke activated carbon adsorbent, KOH alkali fusion preparation method thereof, and application of semicoke activated carbon adsorbentin removal of tetracycline in water
CN111167407A
Method for preparing uranium-adsorbing material with oil shale semi-coke as raw material
CN105879835A
Preparation and application of coal pitch substrate-like mesoporous carbon
CN108584949A